2005
DOI: 10.1007/s11274-004-8026-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of a Metalloprotease from Sorghum Malt Variety KSV8-1

Abstract: A metalloprotease from sorghum malt variety KSV8-I was purified by a combination of 4-M sucrose fractionation, ion-exchange chromatography on Q-Sepharose (Fast flow), gel-filtration chromatography on Sephadex G-100 and hydrophobic interaction chromatography on phenyl-Sepharose CL-4B. The enzyme was purified 7.9-fold to give a 13.4% yield relative to the total activity in the crude extract and a final specific activity of 2128.7 U mg )1 protein. SDS-PAGE revealed a single migrating protein band corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…A Lineweaver-Burk plot for casein was linear suggesting that the rate of proteolysis was The Km value of the present report is also lower than reported by other workers obtained from protease enzymes of some other plants like field bean seeds enzyme 0.0105M (Paul & Gowda, 2000), 0.107M from Moringa oleifera leaves (Banik et al, 2018), 0.02M from the seeds of Cucumismelovaragrestic (Devi & HemaLatha, 2014) and 0.19M from Yemeni bean seeds (Maqtari, Naji, & Ali). However, the value of Vmax is higher in the present study as reported in Table 3 than those of calculated from Sorghum malt protease which was 8.2 μmol/minute (Ogbonna & Okolo, 2005), Mentha piperita L protease, 2.94 μmol/minute and Thymus capitatus L protease 1.3 μmol/minute (Atrooz & Alomari, 2020).…”
Section: Determination Of Km and Vmaxcontrasting
confidence: 71%
“…A Lineweaver-Burk plot for casein was linear suggesting that the rate of proteolysis was The Km value of the present report is also lower than reported by other workers obtained from protease enzymes of some other plants like field bean seeds enzyme 0.0105M (Paul & Gowda, 2000), 0.107M from Moringa oleifera leaves (Banik et al, 2018), 0.02M from the seeds of Cucumismelovaragrestic (Devi & HemaLatha, 2014) and 0.19M from Yemeni bean seeds (Maqtari, Naji, & Ali). However, the value of Vmax is higher in the present study as reported in Table 3 than those of calculated from Sorghum malt protease which was 8.2 μmol/minute (Ogbonna & Okolo, 2005), Mentha piperita L protease, 2.94 μmol/minute and Thymus capitatus L protease 1.3 μmol/minute (Atrooz & Alomari, 2020).…”
Section: Determination Of Km and Vmaxcontrasting
confidence: 71%
“…High levels of metalloproteases were found in sorghum and apparently also cysteine‐ and serine‐type proteases . Both the metallo‐ and cysteine‐type proteases have been purified from sorghum malt. The sorghum malt proteases, like those of barley malt, are insoluble in simple aqueous solvents .…”
Section: Enzymes Of Sorghum Maize and Rice Malt And Whole Raw Grainmentioning
confidence: 99%
“…Greater proteolysis has equally been achieved through the use of cysteine hydrochloride as an extractant with a consequent increase in FAN development 42,43 as well as a better understanding of the physico-chemical, catalytic and molecular properties of the sorghum malt proteases [41][42][43][44][45]47,48 . In some reports, protein modification and mobilisation were significantly optimized through the application of air-resting and alkaline (0.1% NaOH) steeping 50 .…”
Section: Low Fan and Inadequate Proteolysismentioning
confidence: 99%
“…This resulted in its use only as an adjunct in the form of grits or whole grains 26,31,57 , or better still, mashing raw sorghum with some commercial enzymes 2,3,8,13,62 . Using some improved Nigerian sorghum malt varieties, notably SK5912, KSV8 and ICSV400, it is noteworthy and indeed salutary to report that more than 80% of the biochemical problems of sorghum malt have been resolved through conscientious research efforts [18][19][20][41][42][43][44][45][46][47][48]51 . Highlights of these exciting results are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%